Tetrameric structure of SUR2B revealed by electron microscopy of oriented single particles. - Fotinou, C; Aittoniemi, J; De Wet, H; Polidori, A; Pucci, B; Sansom, MS; Vénien-Bryan, C; Ashcroft, F (2013)
The ATP-sensitive potassium (K(ATP)) channel is a hetero-octameric complex that links cell metabolism to membrane electrical activity in many cells, thereby controlling physiological functions such as insulin release, muscle contraction and neuronal activity. It consists of four pore-forming Kir6.2 and four regulatory sulfonylurea receptor (SUR) subunits. SUR2B serves as the regulatory subunit in smooth muscle and some neurones. An integrative approach, combining electron microscopy and homology modelling, has been used to obtain information on the structure of this large (megadalton) membrane protein complex. Single-particle electron microscopy of purified SUR2B tethered to a lipid monolayer revealed that it assembles as a tetramer of four SUR2B subunits surrounding a central hole. In the absence of an X-ray structure, a homology model for SUR2B based on the X-ray structure of the related ABC transporter Sav1866 was used to fit the experimental images. The model indicates that the central hole can readily accommodate the transmembrane domains of the Kir tetramer, suggests a location for the first transmembrane domains of SUR2B (which are absent in Sav1866) and suggests the relative orientation of the SUR and Kir6.2 subunits.